Oral presentation Bioprocess development for the production of succinic acid from orange peel waste - Vasquez Christodoulou, Marlen (My University, 2026)
Patsalou M, Pateraki C, Vasquez MI, Drouza C, Koutinas M, Bioprocess development for the production of succinic acid from orange peel waste, Oral presentation, 4th International Conference on Sustainable Solid Waste Management, Limassol, Cyprus, 23-25 June 2016.